Stakeholders Management. Application in Local Governments for Productivity and Competitiveness - Rojas Palacios, Luis Eden (2021)
In Peru there are few research works on stakeholder management in local governments, for this, a systematic literature search was carried out based on known data, using keywords and information analysis. The objective was to identify trends in Stakeholder Management or interest group implemented in public management contexts to increase social productivity and competitiveness. The systematic review carried out led to the identification of 14 published articles; the same ones that were subjected to a reading and analysis process. Various databases were accessed (Scopus, Scielo, Google Academic, etc.) that contained indexed journals, information was obtained using Boolean operators, the results obtained show that there is a tendency to dialogue and the commitment assumed by each stakeholder and that it will increase productivity, competitiveness in improving performance levels, generating positive and sustainable impacts on local governments.